2014
DOI: 10.1371/journal.pone.0109154
|View full text |Cite
|
Sign up to set email alerts
|

Break CDK2/Cyclin E1 Interface Allosterically with Small Peptides

Abstract: Most inhibitors of Cyclin-dependent kinase 2 (CDK2) target its ATP-binding pocket. It is difficult, however, to use this pocket to design very specific inhibitors because this catalytic pocket is highly conserved in the protein family of CDKs. Here we report some short peptides targeting a noncatalytic pocket near the interface of the CDK2/Cyclin complex. Docking and molecular dynamics simulations were used to select the peptides, and detailed dynamical network analysis revealed that these peptides weaken the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 55 publications
(65 reference statements)
1
17
0
Order By: Relevance
“…MD simulations can be effective in understanding how the two mutations at position 130 perturb the protein structure. The accuracy in computational modeling and MD simulation has made it possible to study processes that are too fast to be observed experimentally [ 25 27 ]. These approaches have been successfully employed to address questions ranging from protein folding to drug design and screening [ 25 , 28 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…MD simulations can be effective in understanding how the two mutations at position 130 perturb the protein structure. The accuracy in computational modeling and MD simulation has made it possible to study processes that are too fast to be observed experimentally [ 25 27 ]. These approaches have been successfully employed to address questions ranging from protein folding to drug design and screening [ 25 , 28 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Four allosteric pockets in CDK2 have been identified crystallographically ( Table 3 ) with ligands bound in each of them [ 63–65 ]. Additionally, two allosteric pockets were putatively discovered by computational methods [ 66 , 67 ]. The best characterized allosteric pocket binds 8-anilino-1-naphthalene sulfonate (ANS), as confirmed by X-ray crystallography [ 63 ].…”
Section: Type III and Iv Allosteric Inhibitorsmentioning
confidence: 99%
“…The other allosteric pockets were discovered computationally at the interface of CDK2 and cyclin E, next to the T-loop [ 67 , 71 ]. Short 5-mer peptide DAALT bind to the interface allosteric pocket with the strongest affinity of K d = 0.5 μM to prevent the protein–protein interaction of CDK2 and cyclins [ 67 ]. Docking studies indicated that C177, K178, and Y180 are three key residues with the highest contribution toward binding these small peptides.…”
Section: Type III and Iv Allosteric Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we utilize the dynamical network analysis to investigate the structural characteristic of the bulb-type mannose binding protein 29 34 . The network analysis reveals that the polar residues on the surface with high closeness are responsible for the long-range recognition of dimer formation.…”
Section: Introductionmentioning
confidence: 99%